Analysis of the Influence of Legal Policy on the Financial Performance of Companies in the Manufacturing Sector: Case Study Using the Anova Method - Sanusi, Sanusi (Journal of Legal and Cultural Analytics, 2024)
This study aims to evaluate the effect of legal policy implementation on the financial performance of companies in the manufacturing sector using a quantitative research design with case studies. The population in this study are manufacturing companies in Indonesia. Sample selection using purposive sampling. The data used are primary data and secondary data by distributing questionnaires using the ANOVA test. The results showed a significant difference in the company's financial performance between the period before and after the implementation of the legal policy, with a p-value of 0.032 (p<0.05). This shows that legal policy has a real impact on the financial performance of companies in the manufacturing sector so that a stable legal framework is needed to encourage optimal financial performance.